Medication Adherence Among Hypertensive Patients in Kurdistan Region of Iraq: An Observational Follow-Up Study - Deldar Morad Abdulah; Saeid Khezer Ahmed; Zuhair Rushdi Mustafa (Medsci Publications, 2024)
Background: Adherence to medications is a main concern to hypertension control and incidence of CVD complications. This study aimed to measure the level of medication adherence of hypertensive patients after one month follow-up. Methods: An observational one-month follow-up study was conducted in 93 hypertensive patients in Kurdistan Region. Results: Patients' mean age was 55.03 (25-85 years). The mean value of the MARS score of adherences was 7.68 out of 10. The mean values of dimensions of adherence were 3.20 of 4 (medication adherence behavior), 2.92 of 4 (attitude toward taking medication), and 1.55 of 2 (negative side effects and attitudes to medication). We found that the males, single and married, urban, those with no chronic disease, and those with higher levels of education were more likely to adhere to medication. The patients with shorter disease duration and treatment had higher adherence scores. The patients with no experience of the medication side effects had higher levels of medication adherence (8.80 vs. 7.00; P<0.0001) and patients who took fewer tablets/day. Conclusions: We observed high-adherence level among hypertensive patients. Prolong disease duration, long treatment duration, increase number of tablets/days, and increase number of comorbidities may significantly decrease the medication adherence rate.